Dimensi Mistik Tafsir Ayat-ayat Sakinah dalam Rūḥ al-Maʿānī sebagai Solusi Perceraian - Esse Esse; Nurfiati Nurfiati; Hasani Ahmad Said (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
The high divorce rate in Indonesia highlights the importance of strengthening the spiritual dimension of family life. This study examines the mystical dimensions of the interpretation of the verses on sakinah in al-Ālūsī’s Rūḥ al-Maʿānī using a thematic exegetical approach. It aims to uncover the meaning of sakinah from a mystical perspective and its relevance to family development. Employing a qualitative library research method, the study analyzes Qur’anic verses containing the term sakinah, with particular attention to al-Ālūsī’s interpretations and the Sufi characteristics that shape his thought. The study is based on the assumption that family problems are influenced not only by social and economic factors but also by a weak spiritual dimension that serves as the foundation of family life. The findings reveal that al-Ālūsī interprets sakinah as inner peace that emanates from the Divine Presence and the strengthening of faith. From this perspective, sakinah is regarded as a gift from Allah that nurtures a sense of security, peace of mind, and family harmony. This interpretation reflects a strong Sufi influence and underscores the importance of spirituality in building family resilience. Furthermore, the concept of sakinah in al-Ālūsī’s interpretation remains highly relevant as a spiritual foundation for fostering harmonious families amid the challenges of modern life.